2014
DOI: 10.1515/jpem-2013-0260
|View full text |Cite
|
Sign up to set email alerts
|

A de novo mutation of DAX1 in a boy with congenital adrenal hypoplasia without hypogonadotropic hypogonadism

Abstract: We report the case of a 12-year-old boy with a de novo mutation in the DAX1 gene (for dosage-sensitive sex reversal, congenital adrenal hypoplasia critical region on the X chromosome, gene 1; also called NROB1). He was born at term, Addison's disease was diagnosed at 8 years with a salt-wasting syndrome, and then hydrocortisone substitution was taken; the child continued to develop normally. A reoccurrence of salt-wasting syndrome usually happened after an episode of an abrupt withdrawal of hydrocortisone subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…HH is the most common finding [1,24]. However, delayed or incomplete puberty associated with partial gonadotropin deficiency [1,26,27] or phenotypes with normal gonadotropin function have also been described [12,14,[28][29][30][31]. More puzzling, some have suggested that chronic ACTH stimulus to Leydig cells may be related to gonadotropin-independent precocious puberty phenotype in X-linked AHC boys [28].…”
Section: Discussionmentioning
confidence: 99%
“…HH is the most common finding [1,24]. However, delayed or incomplete puberty associated with partial gonadotropin deficiency [1,26,27] or phenotypes with normal gonadotropin function have also been described [12,14,[28][29][30][31]. More puzzling, some have suggested that chronic ACTH stimulus to Leydig cells may be related to gonadotropin-independent precocious puberty phenotype in X-linked AHC boys [28].…”
Section: Discussionmentioning
confidence: 99%
“…The severity of CHH in men with DAX1/NR0B1 mutations can differ within the same family (79,80,82 88,93). Some mutated patients may even have spontaneous puberty and varying degrees of altered spermatogenesis (79,80,82,94).…”
Section: Dax1/nrob1mentioning
confidence: 99%
“…2 AHC is severe unless appropriate steroid replacement therapy is provided; therefore, the diagnosis has important implications for patients and their families. [3][4][5][6][7] The gene responsible for AHC is DAX1 (dosage-sensitive sex reversal, congenital adrenal hypoplasia critical region on the X chromosome, gene 1; also known as NROB1), [8][9][10][11][12][13][14][15][16][17][18][19][20][21] which encodes repressor of steroidogenic factor-1 (SDF1), reduces early growth response-1 (Egr1) and SDF1 synergy, and diminishes gonadotropin-releasing hormone (GnRH) stimulation of the luteinizing hormone beta (LHb) promoter. 22 To date, a wide variety of mutations in DAX1 have been described.…”
Section: Introductionmentioning
confidence: 99%
“…The gene responsible for AHC is DAX1 (dosage-sensitive sex reversal, congenital adrenal hypoplasia critical region on the X chromosome, gene 1; also known as NROB1 ), 8 21 which encodes repressor of steroidogenic factor-1 (SDF1), reduces early growth response-1 (Egr1) and SDF1 synergy, and diminishes gonadotropin-releasing hormone (GnRH) stimulation of the luteinizing hormone beta (LHβ) promoter. 22 …”
Section: Introductionmentioning
confidence: 99%